21 Russian Short Prose from the Odd Century - Lipovetsky, Mark (Cultural Syllabus, 2019)
This collection of Russian short stories from the 21st century includes works by famous writers and young talents alike, representing a diversity of generational, gender, ethnic and national identities. Their authors live not only in Russia, but also in Europe and the US. Short stories in this volume display a vast spectrum of subgenres, from grotesque absurdist stories to lyrical essays, from realistic narratives to fantastic parables. Taken together, they display rich and complex cultural and intellectual reality of contemporary Russia, in which political, social, and ethnic conflicts of today coexist with themes and characters resonating with classical literature, albeit invariably twisted and transformed in an unpredictable way. Most of texts in this volume appear in English for the first time. 21 may be useful for college courses but will also provide exciting reading for anyone interested in contemporary Russia